ทักษะผู้บริหารสถานศึกษาในศตวรรษที่ 21 ที่ส่งผลต่อการปฏิบัติงานตามมาตรฐานวิชาชีพครู สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาชลบุรี เขต 2
The purposes of this research were 1) to examine the level of school administrators’ skills in the twenty-first century, 2) to investigate the level of job performance based on teaching professional standards, 3) to determine the relationship between school administrators’ skills in the twenty-first century and the job performance based on teaching professional standards, and 4) to explore the level of school administrators’ skills in the twenty-first century that affected the job performance based on teaching professional standards. The participants in this research were 297 civil teachers under Chonburi Primary Educational Services Area Office 2 in the 2020 academic year. The sample size was obtained by using Krejcie and Morgan’s table, and multi-stage sampling. The data collection instrument was a set of questionnaires. The statistics for data analysis were percentage, standard deviation, Pearson’s product-moment correlation coefficient, and Stepwise multiple regression analysis. The results were as follows: 1) the level of school administrators’ skills in the twenty-first century was overall at the highest level, from high to low: technology use, innovation, and digital literacy, followed by creativity skills. The skills with the least average were communication and information skills; 2) the level of the job performance based on teaching professional standards, overall and in each aspect, was at the highest level, from high to low: teacher performance, followed by learning management. The least average skill was about parent- community-school relationship; 3) The relationship between school administrators’ skills in the twenty-first century and the job performance based on teaching professional standards was at a high level of positive correlation (=.648) with the 0.5 level of significance; and 4) the level of school administrators’ skills in the twenty-first century in terms of technology use, innovation, and digital literacy, creativity, and teamwork affecting the job performance based on teaching professional standards at the 0.5 level of significance. The predictive equation could be written as standard scores as = .352 +191 +.167 , number=90, journal=Journal of Graduate School Sakon Nakhon Rajabhat University, author=Srichan, Tawatchai and Aiemphaya , Kanporn and Noymanee, Niwat, year=2023, month=Sep., pages=26–40